Design of meta surface-based patch antenna by using multi-port power divider for wireless advanced communications - Vanitha Rani Rentapalli; Bappadittya Roy (Penerbit Universiti Kebangsaan Malaysia, 2024)
The compact Multi-Port Power Divider is presented based on the microstrip patch resonator. To explicate its mode of operation, the resonant property of the circular microstrip antenna is illustrated for multi-port power divider operation. This MPPD is constructed with two aligned patch resonators with a meta surface to control the radiation parameters. In this paper, the functional description of the power divider along with the meta surface can be exemplified by the field distributions of the resonating ports. The FR4 epoxy substrate material, with a dielectric constant of 4.4 and a thickness of 1.6, is used for the antenna to operate at a 2.4 GHz resonating frequency, with an antenna size of 0.4 λ0×0.48 λ0×0.128 λ0, also having a bandwidth of 2.2GHz to 2.6GHz with a gain of 5dBi, along with an axial ratio below 3dB at the reflection coefficient of -40dB. The presence of meta surface in microstrip antenna increases the bandwidth and valued gain at certain extent, it further improves the functionality of the overall system. The performance of the proposed antenna was analyzed with the E and H planes of the radiation pattern, with improved gain obtained in the presence of a meta surface-based microstrip antenna. The meta surface appeared in the form of a mesh type of structure, fed by a microstrip antenna revealing a good agreement with the simulated one. The measured result shows that the proposed antenna has the perfect axial ratio along with a 10dB impedance bandwidth achieved with a valued gain of 5to 11dBi